Ecophilosophy and the natural environment - Hull, Zbigniew (Studia Ecologiae et Bioethicae, 2006)
The article contains a semantic analysis of the terms of eco-philosophy, and discusses this theme widely as well as closely presenting the relation between a human being and the natural environment.